2022
DOI: 10.3390/jmse10121963
|View full text |Cite
|
Sign up to set email alerts
|

Operational Modal Analysis of Offshore Wind Turbine Tower under Ambient Excitation

Abstract: The condition of an offshore wind turbine (OWT) should be monitored to assure its reliability against various environmental loads and affections. The modal parameters of the OWT can be used as an indicator of its condition. This paper combines the Kalman filter, the random decrement technique (RDT), and the stochastic subspace identification (SSI) methods and proposes an RDT-SSI method to estimate the operational frequency of an OWT subjected to ambient excitation. This method imposes no requirement on the inp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…In addition, scouring decreases the buried depth of the OWT foundation; accordingly, structural dynamic properties change due to the scouring. Thus, structural dynamic characteristics (e.g., frequency, the damping ratio, and mode shapes) are employed as an indicator of the scouring [60][61][62]. Weijtjens et al (2017) analyzed the modal parameters of OWTs and found that the resonance frequency of the second-order mode is most closely related to OWT scouring [62].…”
Section: Scouringmentioning
confidence: 99%
“…In addition, scouring decreases the buried depth of the OWT foundation; accordingly, structural dynamic properties change due to the scouring. Thus, structural dynamic characteristics (e.g., frequency, the damping ratio, and mode shapes) are employed as an indicator of the scouring [60][61][62]. Weijtjens et al (2017) analyzed the modal parameters of OWTs and found that the resonance frequency of the second-order mode is most closely related to OWT scouring [62].…”
Section: Scouringmentioning
confidence: 99%
“…Zhang et al [53] proposed an RDT-SSI method to estimate the operational frequency of an OWT under ambient excitation using combined Kalman filter, the Random Decrement Technique (RDT), and stochastic subspace identification (SSI) methods. RDT technique used to pick up the free-timedecaying signal of a structure having unknown excitation and SSI estimate the modal properties of large-scale turbine having high noise level.…”
Section: B Numerical Simulationsmentioning
confidence: 99%
“…On the contrary, techniques based on stochastic subspace identification (SSI) are well-known input-free methods used to extract modal parameters under ambient excitations. In other words, SSI-based identification techniques can conduct operational modal analysis (OMA) under the assumption of a stationary process using output-only measurements and have numerous applications across the monitoring of bridges, wind turbine towers, and power systems [4][5][6]. The stability and robustness of SSI for noise contamination have been proven [7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%